Die innere Haut. - Fast, Frederike (Herford : MARTa Herford, 2017)
Aminde, Ulf ; Banier, François-Marie ; Bock, John ; Borremans, Michaël ; Bourgeois, Louise ; Bowery, Leigh ; Greer, Fergus ; De Bruyckere, Berlinde ; Cahn, Miriam ; Cumming, Donigan ; Dijkstra, Rineke ; Dumas, Marlene ; Dürer, Albrecht ; Ekici, Nezaket ; Emin, Tracey ; Eva & Adele ; Valie Export ; Gao Brothers ; Garbe, Josephine ; Gelton, Toussaint ; Gilden, Bruce ; Goldin, Nan ; Isaacs, John ; Isenstein, Jamie ; Klauke, Jürgen ; Kluge, Gustav ; Kotatkova, Eva ; Krauss, Clemens ; Kulik, Oleg ; Lienbacher, Ulrike ; Lingelbach, Johannes ; Lucas, Sarah ; Mikhailov, Boris ; Najjar, Michael ; Nashat, Shahryar ; Novarina, Virgile ; Ono, Yoko ; Pasaiko, Oksana ; Prouvost, Laure ; Pylypchuk, Jon ; Pynas, Jan Symonsz ; Reimann, Lotte ; Rosefeldt, Julian ; Rosenbohm, Lars ; Sarcevic, Bojan ; Schneider, Gary ; Seban, Jean ; Sierra, Santiago ; Stark, John ; Teller, Juergen ; Teniers, David ; Tichy, Miroslav ; Towell, Larry ; Trojan, Stefanie ; Wearing, Gillian ; Wurm, Erwin
4 volumes: Essay (79 p. : ill.), Guide (162 p. : ill.), Show (ongepag. : ill.), Index (35 p. : ill.)
kunstcatalogus